FACS: A geospatial agent-based simulator for analysing COVID-19 spread and public health measures on local regions. Issue 4 (4th July 2022) - Mahmood, Imran; Arabnejad, Hamid; Suleimenova, Diana; Sassoon, Isabel; Marshan, Alaa; Serrano-Rico, Alan; Louvieris, Panos; Anagnostou, Anastasia; J E Taylor, Simon; Bell, David; Groen, Derek
ABSTRACT: The recent Covid-19 outbreak has had a tremendous impact on the world, and many countries are struggling to help incoming patients and at the same time, rapidly enact new public health measures such as lock downs. Many of these decisions are guided by the outcomes of so-called Susceptible-Exposed-Infectious-Recovered (SEIR) models that operate on a national level. Here we introduce the Flu And Coronavirus Simulator (FACS), a simulation tool that models the viral spread at the sub-national level, incorporating geospatial data sources to extract buildings and residential areas in a region. Using FACS, we can model Covid-19 spread at the local level, and provide estimates of the spread of infections and hospital arrivals for different scenarios. We validate the simulation results with the ICU admissions obtained from the local hospitals in the UK. Such validated models can be used to support local decision-making for an effective health care capability response to the epidemic.